Effectiveness of Turmeric Ethanol Extract (Curcuma Longa) in Accelerating Wound Healing After in Wistar Rats - Zhou Guoqing; Florenly Florenly; Liena Liena; Johannes Bastira (Budapest International Research and Critics University, 2021)
RISKESDAS results in 2018 showed the DMFT (Decay, Missing and Filled Teeth) index of Indonesian people nationally 2.5% in 2013, rising to 57.6% in 2018. The main cells involved in the wound healing process are fibroblasts. Fibroblasts are stem cells that play a role in forming and putting fibers in the matrix, especially collagen fibers. Turmeric (Curcuma longa) has several pharmacological properties, including anti-inflammatory, anticancer, antioxidant, antiulcus, and antibacterial actions. The content of flavonoids in Curcuma longa, as an immunostimulating substance, then the production of growth hormones such as EGF, TGFα, PDGF, VEGF, FGF, and TGFβ will also increase, so that wound healing can be accelerated. This study was conducted to find out the effectiveness of turmeric ethanol extract (Curcuma Longa) in accelerating wound healing after tooth extraction. This study used 32 male Wistar rats divided into 2 groups, namely the treatment group given turmeric extract (Curcuma Longa) 45% and the treatment group given turmeric (Curcuma Longa) 90%. The wound healing process was assessed by observing fibroblast tissue on the 5th day after the extraction of Wistar mouse teeth. The results of the Chi-Square Test statistical analysis showed a significant difference in the number of fibroblasts in the wound healing process in Wistar rats after tooth extraction between the treatment group given turmeric extract (Curcuma Longa) 45% and the treatment group given Turmeric extract (Curcuma Longa) 90% after the 5th day with p-value (0.032)<0.05). Turmeric extract (Curcuma longa) is 45% and 90% effective in speeding up the healing time of post-extraction wounds of Wistar mouse teeth. Turmeric extract (Curcuma longa) is 90% more effective than turmeric extract (Curcuma longa) 45% in speeding up wound healing time after extraction of rat teeth Wistar because of the flavonoid content in turmeric extract (Curcuma longa) 90% which helps accelerate wound healing higher than turmeric extract (Curcuma longa) 45%.